Age of sexual debut and associated factors among HIV positive individuals registered at anti-retroviral therapy centre of a tertiary hospital of South Gujarat, India - a cross sectional study - Dayama, Sonal; Kosambiya, Jayendra Kumar; Verma, Mamtarani; Ryavanki, Sridhar (International Journal Of Community Medicine And Public Health, 2017)
Background: Evidence shows that early sexual debut “is a significant predictor of prevalent HIV infection”. With this background, this study was planned with objectives of finding the age at sexual debut and to determine mean age of sexual debut, its trend among different age groups and factors associated with it among HIV positive individuals. Methods:A Cross sectional study was conducted at Anti-Retroviral Therapy (ART) centre of a Tertiary Hospital of Gujarat region of India. Two hundred fifty patients were enrolled in the study. Age of sexual debut and associated factors like education, occupation, marital status, substance abuse and condom use at sexual debut were explored. Results: Among 250 participants, 240 (96%) had initiated sexual activity among which 133 (55.4%) were males and 107 (44.6%) were females. Mean age of sexual debut was 19.6 (±3.7) years; among males 21.2 (±3.9) years and females 17.7 (±2.2) years. The lowest age of coital debut was 14 years in males and 13 years in females. Mean age of sexual debut in the younger age group was significantly lower than among the older age group. Age of sexual debut was found to be independent of socioeconomic status, educational status and history of substance abuse; lower age of sexual debut was found to be associated with being a laborer, a migrant or female. Conclusions:Interventions for behaviour change regarding sexual health among vulnerable groups like adolescents, migrants and females need to be intensified.